Research on performance optimization of agricultural intelligent energy meters driven by intelligent sensors under overload conditions - Chengfei Qi; Yan Liu; Yaoyu Wang; Chaoran Bi; Wenwen Li (Measurement: Sensors)
During the actual operation of smart energy meters used in agriculture, there may be situations where current overload (greater than Imax) occurs. Some smart energy meters used in agriculture may experience power reduction or even reverse operation during overload operation. When the current returns to the measurement range, the energy meter is still in an abnormal state. This article starts from the case of on-site operation failure of intelligent energy meters for agriculture, simulates the overflow effect in ADC filters and metering chips, explains the principles of the above two phenomena, and provides solutions. Meanwhile, the correctness of the solution method was verified through experimental data.Corresponding guidance has been provided to provincial power companies regarding the performance requirements of energy meters after overload.